The Role of the Public Prosecutor in the Investigation - Vári, Vince (Magyar Rendészet, 2023)
The study describes the prosecutor’s role in the initiation phase of the criminal procedure: in the preparatory procedure, the powers, tasks, management and supervision activities authorised by the Criminal Procedure Act are presented in detail. In the investigative stages following the preparatory procedure, the study includes an overview and precise delimitation of the conditions under which we can speak separately about the preliminary investigation and the inspection stage. This section emphasises the differences concerning the relationship between the investigating authority and the prosecutor’s office, depending on whether it is a preliminary investigation or an inspection phase. At the end of the study, the prosecutor’s guidance typical of the inspection phase will be described. Precisely fixing the specific powers of the Criminal Procedure Act, determined for the prosecutor to carry out the management tasks of the investigation effectively.